Influence of augmented reality on purchase intention - Anitha Nallasivam; Prabha Kiran (Journal of Management and Science, 2022)
In today’s business competitive environment, organizations are striving to discover innovative ideas in order to support and promote their offerings. In spite of the undeniable fact of traditional marketing to promote a product, it has gradually failed in meeting the prerequisites of the present markets. The association of augmented reality in developing customer brand engagement and purchase intention is the most highlighted element of this study. The purpose of the study is to explore the impact of augmented reality in the creation of customer brand engagement and purchase intention with the effect of value cocreation.The study was conducted through a questionnaire sent to the people living in Bangalore via google forms. Total of 514 data was collected from the people. AMOS was used for the study to come to the conclusion. The paper include the managerial implications, finding and recommendations in respect to the above study.